Analisis Penerbitan Sertifikat Hak Guna Bangunan Atas Tanah Di Sempadan Sungai (Suatu Penelitian Di Gampong Lam Ujong, Kabupaten Aceh Besar) - Ramadhan Ramadhan (Universitas Islam Sumatera Utara, 2022)
PT Hadrah Aceh Pratama has established a subsidized housing area in 2018 in Gampong Lam Ujong, BaitussalamSub-District, Aceh Besar Regency by doing community land acquisitionin Gampong Lam Ujong covering an area of 74,851 m2.The residential area is built bordering the river channel on the north, east and west of the building, while in the south it borders on residents’ land.Based on the news event of the field research on the construction of Hadrah Regency 10 Lam Ujong housing, BaitussalamSub-District, Aceh Besar Regency, it is described that in RTRW map of Aceh Besar Regency which is contained in Qanun Aceh Besar No. 4 year 2013 concerning RTRW of Aceh Besar Regency 2012-2032, that on the West and North sides the location is not mapped as a river area and river border.However, in reality, currently there is a channel that functions as a channel that connects the pond area around the location with the northern sea with varying channel widths.Previously, the channel had a width of ±3 meters, but due to the earthquake and tsunami in Aceh in 2004, the channel was slightly wider.The results of the research obtained are the status of SHGB on the river border in Gampong Lam Ujong, Aceh BesarRegency, administrative defects occur due to the RTRW map of Aceh Besar Regency contained in the Qanun of Aceh Besar